William Howard Taft, an intimate history - Anderson, Judith Icke (Norton New York, 1981)
Based on the author's thesis, UCLA. Includes bibliographical references and index.
Based on the author's thesis, UCLA.
Keywords: Taft, William H. -- 1857-1930; Biography -- United States; 1901-1909 -- United States; 1909-1913 -- United States